Headache in patients with Systemic Lupus Erythematosus: a case- control study - Oliveira, Igor de; Mariz, Henrique de Ataíde; Duarte, Angela Luzia Branco Pinto; Filho, Pedro Augusto Sampaio Rocha (Headache Medicine, 2023)
Full abstract in PDF.